Dense fluidized granular media in microgravity. (December 2017) - Born, Philip; Schmitz, Johannes; Sperl, Matthias
Abstract Handling and transport of granular media are inevitably governed by the settling of particles. Settling into a dense state is one of the defining characteristics of granular media, among dissipation and absence of thermal agitation. Hence, settling complicates the adaptation of microscopic theories from atomic, molecular, or colloidal media to granular media. It is desirable to provide experiments in which selectively one of the granular characteristics is tuned to test suitable adaptation of a theory. Here we show that gas fluidization of granular media in microgravity is a suitable approach to achieve steady states closer to thermally agitated systems free of settling. We use diffusing-wave spectroscopy to compare the spatial homogeneity and the microscopic dynamics of gas-fluidized granular media on the ground and in drop tower flights with increasing packing densities up to full arrest. The gas fluidization on the ground leads to inhomogeneous states as known from fluidized beds, and partial arrest occurs at packing fractions lower than the full arrested packing. The granular medium in microgravity in contrast attains a homogeneous state with complete mobilization even close to full arrest. Fluidized granular media thus can be studied in microgravity with dynamics and packing fractions not achievable on the ground. Granular matter: Coming to rest in low gravity Microgravity provides a better environment to study how grains move when agitated, scientists in Germany show. Philip Born and co-workers from the Institute of Materials Physics in Space demonstrate that microgravity analogue conditions enable studies on particle dynamics at packing densities not achievable on the ground. Dense granular media under external agitation tends to partially arrest on the ground due to particle collision and settling caused by gravity. This diverseness of the medium makes it hard to develop a theory that can describe the general behavior. Born and colleagues use diffusing-wave spectroscopy to compare the spatial homogeneity and microscopic dynamics of granular media on the ground and in drop towers. They show that unlike on the ground, granular media in microgravity conditions can reach a homogeneous state without partial arrest at high packing densities.